A Prospective Study of Magnetic Resonance Imaging Assessment of Post-radiation Changes Following Stereotactic Body Radiation Therapy for Non-small Cell Lung Cancer. Issue 10 (October 2019) - Munoz-Schuffenegger, P.; Kandel, S.; Alibhai, Z.; Hope, A.; Bezjak, A.; Sun, A.; Simeonov, A.; Cho, B.C.J.; Giuliani, M.
Abstract: Aims: Follow-up computed tomography scans after lung stereotactic body radiation therapy (SBRT) are difficult to interpret due to the presence of benign fibrosis, which can make the detection of local recurrence difficult. The objective of this study was to determine the feasibility of a novel thoracic magnetic resonance imaging (MRI) protocol incorporating diffusion-weighted imaging (DWI) and dynamic contrast-enhanced (DCE) imaging for the assessment of the treated lung parenchyma after SBRT. Materials and methods: On a prospective trial, post-treatment MR images were acquired in 30 patients treated with SBRT (divided into three different cohorts according to the likelihood of local recurrence as per an expert panel). These images were assessed by an expert thoracic radiologist blind to clinical data, who indicated local recurrence in a dichotomous manner. Local recurrence was confirmed by biopsy or subsequent growth on follow-up computed tomography scans. Results: Thirty patients underwent MRI as part of this study; 27/30 patients were analysable for local recurrence. MRI was conducted at a median of 27.3 months (range 6.5–71 months) from SBRT. No side-effects resulted from either MRI or contrast administration. At a median follow-up time of 45 months after treatment, three local recurrence episodes have occurred. MRI assessment diagnosed seven patients as having a local recurrence, which was later confirmed in three and did not miss any of the true local recurrences. When comparing apparent diffusion coefficient (ADC) values according to local recurrence, the mean ADC value for the local recurrence-free group was 1770 × 10 −3 mm/s 2 (range 1038–3105 × 10 −3 mm/s 2 ) versus 981 × 10 −3 mm/s 2 (range 926.6–1065 × 10 −3 mm/s 2 ) for the local recurrence group ( P = 0.0014). Conclusions: A novel 3.0 T MRI protocol incorporating DWI and DCE was feasible and confirmed the suspicion of local recurrence in patients with highly suspicious computed tomography scans. This imaging tool could potentially aid in selecting patients for salvage treatment after local SBRT failure. Future work should be pursued to validate these findings. Highlights: There is a need to refine the diagnosis of local recurrence following lung SBRT. Thoracic 3.0T MRI is feasible in patients who have previously received lung SBRT. MRI confirmed recurrence in 3 patients and all patients with a confirmed clinical recurrence were detected by the MRI scan. On an exploratory analysis, ADC values were significantly lower in those patients with recurrence compared with those who did not recur locally after lung SBRT. MRI can potentially increase the specificity of conventional CT imaging for detecting local recurrence after SBRT. Further confirmatory studies are needed.